Government Health Insurance for People Below Poverty Line in India : Quasi-Experimental Evaluation of Insurance and Health Outcomes - Sood, Neeraj; Bendavid, Eran; Mukherji, Arnab; Wagner, Zachary; Nagpal, Somil; Mullen, Patrick (BMJ Publishing, 2019)
The objective of this study is to evaluate the effects of a government insurance program covering tertiary care for people below the poverty line in Karnataka, India, on out-of-pocket expenditures, hospital use, and mortality.